2018
DOI: 10.1101/350587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DiverseEscherichia colilineages, from domestic animals and humans in a household, carry colistin resistance genemcr-1in Ecuador

Abstract: 23The aim of this study was to investigate the presence of Escherichia coli carrying mcr-1 gene 24 in domestic animals close to a child who suffered a peritoneal infection by a mcr-1 positive 25 E. coli. Rectal or cloacal swabs and fecal samples from domestic animals were plated on 26 selective media to isolate colistin-resistant E. coli and isolates were submitted to detection of 27 mcr-1 gene, pulsed field gel electrophoresis (PFGE), multi-locus sequence typing (MLST), 28 replicon typing and S1-PFGE. Four mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Of these STs, ST93 and ST602 were reported to be infrequent in humans but more frequent in animal samples (specifically chicken) [24,76,77], suggesting that the strains of groups ST93 and ST602 were present in chicken, since farming stages and chicken act as reservoirs for these clonal groups. ST2170 was previously reported in retail chicken meat and turkey in Japan and Ecuador, respectively [68,78].…”
Section: Discussionmentioning
confidence: 80%
“…Of these STs, ST93 and ST602 were reported to be infrequent in humans but more frequent in animal samples (specifically chicken) [24,76,77], suggesting that the strains of groups ST93 and ST602 were present in chicken, since farming stages and chicken act as reservoirs for these clonal groups. ST2170 was previously reported in retail chicken meat and turkey in Japan and Ecuador, respectively [68,78].…”
Section: Discussionmentioning
confidence: 80%
“…It was demonstrated that the bacterial isolate from one of the owners presented the same genetic group as 5 isolates from dogs and cats, highlighting the possible transmission of strains carrying this gene between animals and contacting humans. In another study, carried out in Ecuador by Loayza et al (2018), the presence of E. coli carrying the mcr-1 gene was demonstrated in companion animals sharing the same environment as a child with peritoneal infection by mcr-1positive E. coli, suggesting a clonal dissemination, since the detected mcr-1 gene belonged to the same plasmid in all isolates. In view of the aforementioned, it is observed that the presence of the gene in strains isolated from companion animals can be a natural reservoir, introducing another complex form of dissemination in the community (McEwen & Collignon 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Escherichia coli ( E. coli ) lineages having colistin-resistant gene mcr-1 were isolated from domestic animals and humans living in the same household in Ecuador . The results suggested that mcr-1 gene is horizontally transferred amongst E. coli lineages in humans from the domestic animal in the household 10 . Recently, colistin resistant mcr-4 and mcr-5 genes were isolated from the upper and lower alimentary tract of poultry chicken and pigs in China 11 .…”
Section: Introductionmentioning
confidence: 97%